Hyperprogressive disease in non-small cell lung cancer treated with immune checkpoint inhibitor therapy, fact or myth? - Britt, Alec S.; Huang, Caitlyn; Huang, Chao H. (Frontiers in Oncology, 2022)
The therapeutic landscape for patients with non-small cell lung cancer (NSCLC) has dramatically evolved in the last several years with the development and adoption of immune checkpoint inhibitors (ICI) as front-line therapy. These novel antibodies target the interactions in immunoregulatory pathways, such as those between programmed death-1 (PD-1) and programmed death ligand-1 (PD-L1), or cytotoxic T-lymphocyte antigen 4 (CTLA-4) and B7, resulting in the activation of T cells and cytotoxic response to induce an immunologic response in several solid tumor types [1]. ICIs have demonstrated significant survival benefits and sustained responses in the treatment of NSCLC leading to the long-term survival of up to 5 years [2-4]. One unusual response to ICI is a phenomenon termed Hyperprogressive Disease (HYD), which occurs in a subset of patients for whom ICI therapy can induce rapid disease growth, which ultimately leads to poorer outcomes [5]. Existing data suggest an incidence rate ranging from 5 to 37% in NSCLC patients [6-8]. Despite this known entity, a consensus definition for the diagnosis of HYD has not been determined, and the explication of underlying pathophysiologic mechanisms has remained elusive. In this review, we will evaluate recent data on HYD in the NSCLC population, as well as discuss the proposed mechanisms, predictors, and biomarkers potentially implicated in the process.